Ebola [videorecording (DVD)] : the plague fighters - Bienstock, Ric Esther; Keach, Stacy (Nova (Television program), 2007)
When a dreaded outbreak of the deadly Ebola virus swept through a remote region of Zaire in May 1995, Nova was the only film crew permitted to cover the outbreak. The Ebola plague kills a very high percentage of its victims (77% in Kikwit), often by dissolving their internal organs and connective tissue. Learn how disease specialists traced the origins of the outbreak.